FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI LADA DI INDONESIA - Hamdani '; Ermi Tety; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) to know growth of Indonesia’s pepper in the supply and demand on 1990-2013 periods; (2) to analyze the factors who influencing on production of pepper in Indonesia. Analysis method used simultaneous equation with time series data from 1990 till 2013. The results showed that demand and supply of Indonesia’s pepper growth 2,97 percent and 1,00 percent in annual. Demand growth influenced by manufacturing sector and trade, hotel, and restaurant sector. Determinant coefficient (R2) of pepper production is 0,86, F value is 20,16 and dh statistic is -0,81. Production of Indonesia’s pepper significantly influenced by price of Indonesia’s pepper, export of Indonesia’s pepper, interest rate, and production of Indonesia’s pepper previous year. Price of Indonesia’s pepper isn’t responsive in short run and responsive in long run, whereas other variables aren’t responsive in short run and long run.     Keywords: Pepper, Production Factors, Supply and Demand